Kepentingan Ideologis Negara dan Nahdlatul Ulama dalam Pembubaran Hizbut Tahrir Indonesia - Fauzi, Ahmad Irfan; Kosandi, Meidi (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2022)
This article discussed the contestation of ideological interests between the state, Hizbut Tahrir Indonesia (HTI), and Nahdlatul Ulama (NU) in the case of the disbandment of HTI in 2017. The disbandment of HTI explained the existence of pro and contra groups and the attraction of ideological interests. This research was qualitative research with observation and interview methods. The research results proved that there were conflicting and conflicting interests between the interests of the state, HTI, and NU. The state interests were the interests of the Pancasila ideology and public security. NU rejected the caliphate because it was interested in defending the "Islam Nusantara" ideology. NU's success in encouraging the government was influenced by the issues' relevance and the condition of the political structure of Joko Widodo's government for the 2014-2019 period. The polarized condition of the government's political structure in the Jokowi versus Prabowo group influenced the decision to disband HTI because NU was identified with moderate Islam that supported Jokowi. Hence, NU's bargaining power with the Jokowi government was more substantial than HTI.